Understanding Motivational Factors Affecting Entrepreneurial Decision : a Comparison Between Bandung Student Entrepreneurs And Student Non Entrepreneurs - Sihombing, Rodeta; Rachmawati CH, Evy (Journal of Business and Management, 2015)
Abstract. Todayâ€™s students are tomorrowâ€™s potential entrepreneurs. This paper is focused on identify motivational factors that affecting bandung students motivation in becoming an entrepreneur. The objective of the research was to analyse the different motivational factors affecting entrepreneurial and working decision in order to find the proper way to increase the number of student entrereneur. Data was collected using a self administered questionnaire that was distributed through online survey. The population was student from all faculty in Bandung Institute of Technology. The finding of this study show that there is a gap between student entrepereners and non entrepreneurs, it is economic core, and both student show a high motivation in individual core. The results is there is a significant different motivation between student entrepreneurs and student non entrepreneurs. Non-financial and financial support should be improved to university student in Indonesia in order to increase the number of student entrepreneurs.Â Keyword : Entrepreneurial Decision, Motivational Factors, Indonesian student.